Dynamics Psychology of Premarital Sexual Behavior Among Students: A Phenomenological Study - Raisah Zettira Hermawan; Budi Sarasati; Yomima Viena Yuliana (Socrates: Journal of Education, Philosophy and Psychology, 2025)
This study explores the psychological dynamics of premarital sexual behavior among female university students within romantic relationships, using a descriptive phenomenological approach. The research aims to understand how participants experience, interpret, and assign meaning to their involvement in premarital sexual behavior. Two female undergraduate students who had direct experiences with premarital sexual behavior participated in the study, supported by close informants to strengthen data credibility. Data were collected through semi-structured in-depth interviews, observation, and documentation, and analyzed using thematic analysis. The findings reveal that premarital sexual behavior emerged from complex interactions between emotional intimacy, trust in partners, curiosity, environmental normalization, and expectations of long-term commitment. Sexual involvement was interpreted as a form of expressing love, emotional validation, and an effort to maintain romantic relationships. However, an imbalance between high intimacy and passion with unstable commitment generated emotional vulnerability, particularly when participants’ expectations of reciprocity and seriousness were unmet. Feelings of confusion, insecurity, fear of abandonment, and self-doubt were prominent psychological consequences following sexual involvement. This study concludes that premarital sexual behavior among female students cannot be understood merely as risky behavior, but rather as a meaningful psychological experience shaped by emotional needs, relational contexts, and sociocultural influences. A contextual and holistic understanding is essential for developing more empathetic educational and psychological interventions related to sexuality among young adults.